Help-Seeking Experiences of Health Care Learners in a WebCT Online Graduate Study Program - Sherri Melrose; Bonnie Shapiro; Carrie LaVallie (The Canadian Network for Innovation in Education (CNIE), 2005)
This article presents findings from a qualitative research project that explored health care students' activities related to seeking help within a masters program offered exclusively through a WebCT online environment. A constructivist theoretical perspective and an action research approach framed the study. Data sources included one question on a program satisfaction questionnaire, focus groups and ten individual audio tape-recorded transcribed interviews. Content was analyzed for themes and confirmed through ongoing member checking with participants. The following four overarching themes were identified and are used to explain and describe significant features of help-seeking experiences of online health care learners: (1) Self-help included reflection and re-reading directions available within the course; (2) A primary source of help was other students in the class; (3) Involving family, friends and co-workers provided important educational support; and (4) Instructors' first message, involvement in weekly discussions and anecdotal comments were highly valued.